Pseudolaguvia meghalayaensis, a new diminutive sisorid catfish (Teleostei: Siluriformes) from Northeastern India - Lokeshwor, Yumnam; Marak, Pringranchi Dokgre (Zootaxa, 2022)
Pseudolaguvia meghalayaensis, a new diminutive sisorid catfish, is described from the confluence of Rongkil and Rongdal streams (tributaries of the Brahmaputra River) in Meghalaya, India. It is distinguished from its congeners by a combination of characters: striae in thoracic adhesive apparatus strongly anastomosing and break up into small rounded plaques posteromedially, smooth anterior edge of dorsal spine, 8 branched pectoral-fin rays, supraoccipital spine not reaching nuchal shield, pectoral-fin length 17.1–20.1% standard length (SL), predorsal length 40.4–43.8% SL, preanal length 71.1–73.1% SL, body depth at anus 15.6–18.1% SL, anal-fin base length 12.2–12.7% SL, and post adipose fin length12.3–12.6% SL.